(15x-23)+(8x+12)=180

Simple and best practice solution for (15x-23)+(8x+12)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15x-23)+(8x+12)=180 equation:


Simplifying
(15x + -23) + (8x + 12) = 180

Reorder the terms:
(-23 + 15x) + (8x + 12) = 180

Remove parenthesis around (-23 + 15x)
-23 + 15x + (8x + 12) = 180

Reorder the terms:
-23 + 15x + (12 + 8x) = 180

Remove parenthesis around (12 + 8x)
-23 + 15x + 12 + 8x = 180

Reorder the terms:
-23 + 12 + 15x + 8x = 180

Combine like terms: -23 + 12 = -11
-11 + 15x + 8x = 180

Combine like terms: 15x + 8x = 23x
-11 + 23x = 180

Solving
-11 + 23x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 23x = 180 + 11

Combine like terms: -11 + 11 = 0
0 + 23x = 180 + 11
23x = 180 + 11

Combine like terms: 180 + 11 = 191
23x = 191

Divide each side by '23'.
x = 8.304347826

Simplifying
x = 8.304347826

See similar equations:

| 65+195(x-1)=2405 | | 0.35*x+1.6=-0.5 | | -71+5x=48-2x | | 4x+12=5x+9-x+3 | | -71+5c=48-2x | | 65+195x= | | (2x+7)+32=5x-15 | | -4=-1-4 | | 2a+3b+3c=74 | | 12x-153=2x+77 | | 11(y+4)=66 | | 9x^2-6x+1=18x^2-2 | | 18-(6-10y)=4(2y-6)-8 | | -4=-4*-1 | | -8x+2y=5 | | 24a^3+3b^3= | | 4+2x-8x+10+11x=-1 | | -6x-18=33-9x | | -5y+6=-12+62 | | -5+2v=-1 | | 4/16=x/35 | | 3x+76=8x-14 | | 5(x-4)-2(x+5)=15 | | x^3-xy+y^3=1 | | x+3=2XA+7 | | 4q/7=1/5 | | 9(y+3)-5(2y-4)=47 | | 9x-116=-4x+105 | | 8-3(2-n)-17= | | X+2x=1/2x+15 | | 3x+90+2x=180 | | 30a+8-23a=15+10a-20 |

Equations solver categories